Understanding Psammophory in Raphanus sativus and Lagenaria siceraria: An Approach to Reduce Herbivory - Kaushik, Charu; Katiyar, Ratna (Indian Forester, 2022)
Sand entrapment on plant surfaces, termed psammophory is a widely known trait of the plants having significance in reducing herbivory and regarded as one of the potential plants defense phenomena. Trichomes protruding from the surface of leaves and stems defend plants from many herbivores. These trichomes of plants often entrap sand on their surfaces or release some exudates on which sand can get adhered, this phenomenon of carrying sand on their surfaces is called psammophory. Sand and soil are naturally nonnutritive and most of the herbivores find them difficult to process. The presence of these substances (soil, sand) increases the plant defense and reduce herbivory. There is lack of studies for investigating the impact of psammophory on economic plants including vegetables. The current study attempts to understand the benefit of the psammophoric properties of soil and sand in reducing the attacks of herbivores on radish (Raphanus sativus) and bottle gourd (Lagenaria siceraria). Both of these species suffer a heavy loss in their yield due to cabbage borer (Hellula undalis Fabr.) and western striped cucumber beetle (Acalymma vittata), respectively. The current study examined whether presence of sand on these plant surfaces physically protected them from herbivores.